Identifikasi Bakteri dan Jamur pada Makanan dan Minuman Menggunakan Metode Polymerase Chain Reaction (PCR) dan Analisis Deoxyribonucleic Acid (DNA) Molekuler - Devina Chandra; Manuppak Irianto Tampubolon; Monica Suryani; Supartiningsih Supartiningsih (Lembaga Pengembangan Kinerja Dosen, 2026)
Contamination of food and beverages by pathogenic bacteria and spoilage fungi remains a major public health concern, particularly in traditional and street-vended products where hygienic control is often inadequate. Conventional culture-based identification methods are time-consuming and often fail to detect slow-growing or non-culturable microorganisms. This study aimed to identify bacterial and fungal contaminants in food and beverage samples using Polymerase Chain Reaction (PCR) combined with molecular Deoxyribonucleic Acid (DNA) analysis. Samples were collected from local food vendors, and total genomic DNA was extracted using a commercial extraction kit. Bacterial identification targeted the 16S rRNA gene, while fungal identification targeted the Internal Transcribed Spacer (ITS) region, both amplified by PCR and visualized by agarose gel electrophoresis. Amplicons were sequenced and compared with reference sequences in the GenBank database using the Basic Local Alignment Search Tool (BLAST). The results revealed the presence of pathogenic and spoilage microorganisms, including Escherichia coli, Staphylococcus aureus, Salmonella sp., and Aspergillus species, indicating inadequate sanitation during food handling and storage. These findings confirm that PCR-based molecular analysis provides a rapid, sensitive, and specific approach for detecting microbial contamination in food and beverages.